2018
DOI: 10.1007/s00128-018-2407-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Non-destructive Techniques to Measure Mercury (Hg) Concentrations in Gravid Blanding’s Turtles (Emydoidea blandingii) in Northeastern Illinois

Abstract: Aquatic turtles are suitable biomonitors of wetland ecosystem health because they are long-lived and occupy elevated trophic positions in wetland food webs. This study aimed to determine Hg exposure in adult Blanding's turtles (Emydoidea blandingii), an imperiled prairie-wetland species endemic to the northern U.S. and southern Canada. Claw samples were collected from gravid females from four wetland sites in northeast Illinois. Claw Hg concentrations ranged from 654 to 3132 ng/g and we found no effect of body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, due to their status as endangered species, this type of sampling is not viable for monitoring programs, while the use of non-invasive methods such as blood and keratinized matrices (e.g., scutes and nails) allows periodic monitoring (Sakai et al 2000 ; Day et al 2005 ; Bezerra et al 2012 ; Rodríguez-Gutiérrez et al 2020 ). Both tissue types can show more recent (e.g., blood) and longer term (e.g., scutes and nails) exposure (Day et al 2005 ; Benjamin et al 2018 ), characterizing bioaccumulation, patterns of temporal exposure to Hg and other trace metals (Bezerra et al 2012 ; Schneider et al 2015 ; Barraza et al 2019 ; Villa et al 2019 ). The study conducted by Day et al ( 2005 ), found in the loggerhead sea turtle ( Caretta caretta ) along the southeastern coast of the United States a relationship between Hg concentrations in blood and scute samples and the foraging areas with greater contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to their status as endangered species, this type of sampling is not viable for monitoring programs, while the use of non-invasive methods such as blood and keratinized matrices (e.g., scutes and nails) allows periodic monitoring (Sakai et al 2000 ; Day et al 2005 ; Bezerra et al 2012 ; Rodríguez-Gutiérrez et al 2020 ). Both tissue types can show more recent (e.g., blood) and longer term (e.g., scutes and nails) exposure (Day et al 2005 ; Benjamin et al 2018 ), characterizing bioaccumulation, patterns of temporal exposure to Hg and other trace metals (Bezerra et al 2012 ; Schneider et al 2015 ; Barraza et al 2019 ; Villa et al 2019 ). The study conducted by Day et al ( 2005 ), found in the loggerhead sea turtle ( Caretta caretta ) along the southeastern coast of the United States a relationship between Hg concentrations in blood and scute samples and the foraging areas with greater contamination.…”
Section: Resultsmentioning
confidence: 99%
“… Blood >95% ww or dw THg Assumed to be >95% MeHg based on other vertebrates. Sea turtles Scutes, carapace fragments, and nails ~10% fw (or dw if scutes need washing) THg Rodriguez et al ( 2019 ); Benjamin et al ( 2018 ) While scutes are keratinized material the %MeHg may be relatively low and needs more data. Blood >95% ww or dw THg Assumed to be >95% MeHg based on other vertebrates.…”
Section: Methodsmentioning
confidence: 99%
“…3). In contrast, keratinized tissues of vertebrates such as hair/fur, feathers and claws generally display high Hg concentrations due to the affinity of Hg for the sulfhydryl groups contained in keratins (Appelquist et al 1984, Schneider et al 2012Benjamin et al, 2018;Treu et al, 2018;Albert et al, 2019).…”
Section: Thg Concentration: Scute Keratin Layers Vs Full Scutesmentioning
confidence: 99%
“…One method of monitoring land use effects on wetland health is testing for the presence of heavy metals in freshwater turtles. Using non-destructive methods by collecting external tissues (e.g., blood and toenails) eliminates the negative impacts on individuals or populations (Smith et al 2016;Benjamin et al 2018). These external tissues have been found to be positively correlated with concentrations found in internal, more invasive tissues such as liver and muscle (Smith et al 2016).…”
Section: Introductionmentioning
confidence: 99%